Association of Blood Glucose Control and Outcomes in Patients with COVID-19 and Pre-existing Type 2 Diabetes - Zhu, Lihua; She, Zhi-Gang; Cheng, Xu; Qin, Juan-Juan; Zhang, Xiao-Jing; Cai, Jingjing; Lei, Fang; Wang, Haitao; Xie, Jing; Wang, Wenxin; Li, Haomiao; Zhang, Peng; et al. (Cell metabolism, 2020)
Type 2 diabetes (T2D) is a major comorbidity of COVID-19. However, the impact of blood glucose (BG) control on the degree of required medical interventions and on mortality in patients with COVID-19 and T2D remains uncertain. Thus, we performed a retrospective, multi-centered study of 7,337 cases of COVID-19 in Hubei Province, China, among which 952 had pre-existing T2D. We found that subjects with T2D required more medical interventions and had a significantly higher mortality (7.8% versus 2.7%; adjusted hazard ratio [HR], 1.49) and multiple organ injury than the non-diabetic individuals. Further, we found that well-controlled BG (glycemic variability within 3.9 to 10.0 mmol/L) was associated with markedly lower mortality compared to individuals with poorly controlled BG (upper limit of glycemic variability exceeding 10.0 mmol/L) (adjusted HR, 0.14) during hospitalization. These findings provide clinical evidence correlating improved glycemic control with better outcomes in patients with COVID-19 and pre-existing T2D. [Display omitted] •A cohort of 7,337 COVID-19 patients with or without diabetes was retrospectively studied•Diabetes status increased the need for medical interventions during COVID-19•Diabetes status increased the mortality risk of patients with COVID-19•Well-controlled blood glucose correlated with improved outcomes in infected patients Type 2 diabetes (T2D) correlates with a worse outcome for COVID-19. Here, Zhu et al. show that among ∼7,300 cases of COVID-19, T2D is associated with a higher death rate, but diabetics with better controlled blood glucose die at a lower rate than diabetics with poorly controlled blood glucose.